Psychological First Aid Well-Being Support Rounds for Frontline Healthcare Workers During COVID-19 - Malik, Mansoor; Peirce, Jessica; Wert, Michael Van; Wood, Cynthia; Burhanullah, Haroon; Swartz, Karen (Frontiers in Psychiatry, 2021)
Background and Objective: Frontline healthcare workers face unprecedented stress from the current SARS COV-2 (COVID-19) pandemic. Hospital systems need to develop support programs to help frontline staff deal with this stress. The purpose of this article is to describe a support program for front line healthcare workers. Methods: In this community case report, we describe a well-being support rounding program that was developed to deliver Psychological First Aid (PFA) to frontline healthcare workers in a large urban medical center to maintain their sense of psychological well-being and self-efficacy. A team of clinicians from the department of psychiatry, who were trained on the Johns Hopkins RAPID model (Reflective Listening, Assessment, Prioritization, Intervention, and Disposition) to provide PFA, were deployed throughout the hospital. These clinicians carried out daily well-being rounds from April to June during the peak of the pandemic. Results: Approximately 20% of the frontline staff members were going through an acute crisis and benefited from PFA. Anxiety, anger, exhaustion, economic worry, job insecurity, dehumanized interactions with patients due to Personal Protective Equipment (PPE), and stress of taking care of sick and dying patients without their families present, were the main themes identified by the staff. The deployed team used active listening, mindfulness, validation, reframing and other cognitive interventions to support staff. Conclusions: Our experience suggests that frontline staff are willing to engage with in-person, on-site support programs. Fostering resilience and self-efficacy through PFA is a useful model to provide emotional support to frontline healthcare workers during health crises.